(untitled) (Research, Society and Development, 2021)
Introduction: The use of organophosphates is present throughout the world in agriculture, industry and even in domestic environments. Many people are exposed to these pesticides, especially the agricultural population, which is subject to their effects. Objective: to carry out a systematic literature review of articles that evaluated chronic exposure to low doses of organophosphates in rural populations. Methodology: The methodology used was the PICo5 approach and its technical procedure was the systematic literature review, following the steps described in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Results: The databases of the journals consulted, using the keywords “rural populations” and “organophosphates”, resulted in 61 valid scientific articles, of which 22 met the eligibility criteria and were included in this review. The problems studied consider the exposure time, the types of organophosphates, the effects on workers’ health and the use of Personal Protective Equipment, and the benefits of the topic are related to understanding the implications of chronic exposure to organophosphates, which still lacks of studies. Conclusion: Among the most commonly found clinic, there was convergence for effects on the central nervous system and oncologic resulting from this type of exposure.